Subcutaneous abatacept in patients with polyarticular-course juvenile idiopathic arthritis: results from a phase III open-label study - Brunner, Hermine I.; Lutz, Thomas (Arthritis & rheumatology, 2018)
Objective To investigate the pharmacokinetics, effectiveness, and safety of subcutaneous (SC) abatacept treatment over 24 months in patients with polyarticular-course juvenile idiopathic arthritis (JIA). Methods In this phase III, open-label, international, multicenter, single-arm study, patients with polyarticular JIA (cohort 1, ages 6–17 years and cohort 2, ages 2–5 years) in whom treatment with ≥1 disease-modifying antirheumatic drug was unsuccessful received weight-tiered SC abatacept weekly: 10 to <25 kg (50 mg), 25 to <50 kg (87.5 mg), ≥50 kg (125 mg). Patients who had met the JIA–American College of Rheumatology 30% improvement criteria (achieved a JIA-ACR 30 response) at month 4 were given the option to continue SC abatacept to month 24. The primary end point was the abatacept steady-state serum trough concentration (Cminss) in cohort 1 at month 4. Other outcome measures included JIA-ACR 30, 50, 70, 90, 100, and inactive disease status, the median Juvenile Arthritis Disease Activity Score in 71 joints using the C-reactive protein level (JADAS-71–CRP) over time, safety, and immunogenicity. Results The median abatacept Cminss at month 4 (primary end point) and at month 24 was above the target therapeutic exposure (10 μg/ml) in both cohorts. The percentage of patients who had achieved JIA-ACR 30, 50, 70, 90, or 100 responses or had inactive disease responses at month 4 (intent-to-treat population) was 83.2%, 72.8%, 52.6%, 28.3%, 14.5%, and 30.1%, respectively, in cohort 1 (n = 173) and 89.1%, 84.8%, 73.9%, 58.7%, 41.3%, and 50.0%, respectively, in cohort 2 (n = 46); the responses were maintained to month 24. The median (interquartile range) JADAS-71–CRP improved from baseline to month 4: cohort 1, from 21.0 (13.5, 30.3) to 4.6 (2.1, 9.4); cohort 2, from 18.1 (14.0, 23.1) to 2.1 (0.3, 4.4). Improvements were sustained to month 24, at which time 27 of 173 patients (cohort 1) and 11 of 22 patients (cohort 2) had achieved JADAS-71–CRP remission. No unexpected adverse events were reported; 4 of 172 patients (2.3%) in cohort 1 and 4 of 46 (8.7%) in cohort 2 developed anti-abatacept antibodies, with no clinical effects. Conclusion Weight-stratified SC abatacept yielded target therapeutic exposures across age and weight groups, was well tolerated, and improved polyarticular JIA symptoms over 24 months.
Gesehen am 17.10.2019